2022
DOI: 10.1167/iovs.63.11.4
|View full text |Cite
|
Sign up to set email alerts
|

The Fovea-Protective Impact of Double-Layer Sign in Eyes With Foveal-Sparing Geographic Atrophy and Age-Related Macular Degeneration

Abstract: Purpose The purpose of this study was to investigate the impact of double-layer sign (DLS) on geographic atrophy (GA) progression in eyes with foveal-sparing GA and age-related macular degeneration (AMD). Methods This is a retrospective, consecutive case series of eyes with foveal-sparing GA secondary to AMD with more than 6 months of follow-up. The size of the foveal-sparing area was measured on the fundus autofluorescence images at the first and last visits. Each eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The fovea plays the most crucial role in central vision, at which visual acuity is at its highest; thus, certain protective mechanisms could compensate for the effect of mechanical stretching on the fovea. A similar phenomenon has been reported for foveal-sparing geographic atrophy [ 44 ]. Jonas et al [ 45 ] reported that retinal thinning was most apparent in the equatorial and pre-equatorial regions in myopic axial elongation, whereas foveal retinal thickness was mostly unaffected.…”
Section: Discussionsupporting
confidence: 84%
“…The fovea plays the most crucial role in central vision, at which visual acuity is at its highest; thus, certain protective mechanisms could compensate for the effect of mechanical stretching on the fovea. A similar phenomenon has been reported for foveal-sparing geographic atrophy [ 44 ]. Jonas et al [ 45 ] reported that retinal thinning was most apparent in the equatorial and pre-equatorial regions in myopic axial elongation, whereas foveal retinal thickness was mostly unaffected.…”
Section: Discussionsupporting
confidence: 84%
“…As a matter of fact, previous studies reported a protective effect of DLS in atrophy, postulating the existence of a “neochoriocapillaris” that provides support to the outer retina and photoreceptors. 18,27,32…”
Section: Discussionmentioning
confidence: 99%
“…The sample size calculation was determined considering the previous literature on GA area changes in a population with foveal sparing with or without a DLS. 18 The estimated total sample size was 45 patients (paired t -test, two-sided), with a significance level of 1% and a power of 95%. Quantitative data were reported as mean ± SD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative SD-OCT assessments included identification of subretinal drusenoid deposits (SDD; ≥ 3 lesions identified on one B-scan), 10 , 11 refractile drusen (≥ 1 lesion identified on one B-scan), 12 and the double layer sign (DLS). 13 , 14 DLS exceeding 1000 µm in length and 100 µm in height on horizontal B-scan, or exhibiting multiple reflective layers between the RPE and the Bruch's membrane (BM), were excluded to mitigate the risk of confounding by non-exudative MNV.…”
Section: Methodsmentioning
confidence: 99%